Persepsi Siswa Terhadap Nilai-Nilai Islam Dalam Lembar Kerja Peserta Didik (LKPD) Di MTSN 2 Bukittinggi - Recy Wulan Dari; Tengku Tiara Insan Ramadhani; M. Imamuddin (KOLONI, 2024)
Islamic values ​​in mathematics learning can be developed using various methods, one of which is by integrating Islamic values ​​in the learning process. This research aims to determine students' perceptions of Islamic integrated LKPD. The type of research carried out is qualitative descriptive research. The data collection techniques used were Islamic integrated LKPD and a questionnaire about student perceptions. The population in this study were class VII students at MTsN 2 Bukittinggi, while the samples taken were class VII.1 students with a total of 28 students. The technique used in sampling is random sampling technique. The results of the research show that: 1) the understanding aspect of most students agree with a percentage of 48% 2) the assessing aspect of most students agree with a percentage of 57% 3) the presentation aspect of most students agree with a percentage of 61%.